2017
DOI: 10.3389/fpsyg.2017.01101
|View full text |Cite
|
Sign up to set email alerts
|

Parenting with PTSD: A Review of Research on the Influence of PTSD on Parent-Child Functioning in Military and Veteran Families

Abstract: Posttraumatic stress disorder (PTSD) is strongly associated with exposure to war related trauma in military and veteran populations. In growing recognition that PTSD may influence and be influenced by social support and family systems, research has begun to explore the effects that war related trauma and the ensuing PTSD may have on varied aspects of close relationship and family functioning. Far less research, however, has examined the influence of war-related PTSD on parent-child functioning in this populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
91
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 38 publications
8
91
1
1
Order By: Relevance
“…Specifically, we exploit the fact that Colombia has a long and well documented history of civil conflict that has affected large parts of the country and, in particular, rural areas. It is well documented that exposure to violence can cause emotional detachment, which can impede or make subsequent interaction with one's own children harder (Betancourt, 2015;Creech and Misca, 2017, for related evidence). This leads us to consider maternal exposure to past conflict as a potential instrument for current quality time investment, where we exploit variation in the intensity of conflict across municipalities.…”
Section: Choice Of Instrumentsmentioning
confidence: 99%
“…Specifically, we exploit the fact that Colombia has a long and well documented history of civil conflict that has affected large parts of the country and, in particular, rural areas. It is well documented that exposure to violence can cause emotional detachment, which can impede or make subsequent interaction with one's own children harder (Betancourt, 2015;Creech and Misca, 2017, for related evidence). This leads us to consider maternal exposure to past conflict as a potential instrument for current quality time investment, where we exploit variation in the intensity of conflict across municipalities.…”
Section: Choice Of Instrumentsmentioning
confidence: 99%
“…Similarly, observations of interactions between asylum seekers and their children reveal positive associations between PTSD severity and insensitive, unstructured, and hostile parenting behaviors during free play (van Ee et al 2012). Although several studies suggest that mothers exposed to trauma, including those who do not go on to develop significant psychopathology, may compensate for the potential effects of trauma by increasing positive parenting behaviors (e.g., Casanueva et al 2008;Letourneau et al 2007;Levendosky et al 2000Levendosky et al , 2003, most literature points to PTSD as having a detrimental impact on parent-child relations (see Creech and Misca 2017;van Ee et al 2015 for reviews).…”
Section: Ptsd and Parentingmentioning
confidence: 99%
“…Moreover, data from the National Comorbidity Study show that nearly three-quarters of individuals meeting criteria for PTSD are mothers (Nicholson et al 2002). This figure is concerning, in part, because of the potential systemic impact of PTSD that can extend to survivors' interpersonal relationships (e.g., Monson et al 2010), which include impaired parent-child interactions among adults with PTSD (e.g., Creech and Misca 2017;DiLillo and Damashek 2003;Leen-Feldner et al 2011). However, relatively little research has examined factors that may mediate relations between maternal PTSD and parenting difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…The effect size was highest for children of parents with histories of interpersonal trauma, including family violence, community violence and traumatic loss [13]. A recent review, examining the impact of PTSD on parenting behaviour and children's outcomes in military and veteran families demonstrated that PTSD symptoms in parents have an effect on internalising and externalising symptoms in their children, including depression, anxiety, and adjustment problems [14]. This review also indicated an association between parental PTSD symptoms and parent-child functioning difficulties, such as communication problems and less positive parental engagement [14].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review, examining the impact of PTSD on parenting behaviour and children's outcomes in military and veteran families demonstrated that PTSD symptoms in parents have an effect on internalising and externalising symptoms in their children, including depression, anxiety, and adjustment problems [14]. This review also indicated an association between parental PTSD symptoms and parent-child functioning difficulties, such as communication problems and less positive parental engagement [14]. Another systematic review focusing on intergenerational effects of trauma in refugee families demonstrate that the effect on children was diverse but mostly negative [15].…”
Section: Introductionmentioning
confidence: 99%